AB1017 Iliac wing fracture: An unusual osteoporotic fracture. (23rd January 2014) - Casado, E.; Vázquez, I.; Larrosa, M.; Galisteo, C.; Torner, P.; Gratacόs, J.
Abstract : Background: Pubic rami or sacral fractures are insufficiency fractures relatively frequent among patients with osteoporosis. However iliac wing fractures are rare, and most cases reported in the literature correspond to previously treated patients with osteoporosis and previous fractures in other sites 1 . Objectives: To describe the clinical and radiological features of patients with iliac wing fractures diagnosed at the University Hospital of Sabadell in the last 20 years. Methods: Descriptive study. A review of medical records of all out-patients with pelvic fractures referred for diagnosis and treatment of osteoporosis to the Rheumatology department, University Hospital of Sabadell (reference population 400, 000) since 1990. We selected those with the diagnosis of insufficiency fracture of the iliac wing (without trauma or falling from one's own height). After confirming the presence of the iliac wing fracture we proceeded to review the patient's medical history to record clinical and demographic data. Phospho-calcium metabolism parameters and thoracic and lumbar X-ray were also reviewed in all the patients at the time of the fracture. Results: We found 5 iliac wing fractures in 4 patients (3 women). Mean age 58.8±2.8 years (range 43-73). One patient had a simultaneous bilateral fracture. In three cases there were pelvic ring concomitant fractures (pubic rami and/or sacrum). No patient had been previously diagnosed with osteoporosis or fractures. All patients had mechanical pain in their buttock or groin. Risk factors for fractures, other than age, were found in three patients: hyperthyroidism in one case, HIV infection and antiretroviral therapy in the second case, and rheumatoid arthritis under chronic glucocorticoids in the third case. Three of the four patients had hypovitaminosis D (25(OH)D <25 ng/ml), whereas PTH was normal in all cases. No patient had morphometric vertebral fractures. Conclusions: The iliac wing fractures in our series are mostly in postmenopausal women previously undiagnosed and untreated for osteoporosis, with concomitant pelvic ring fractures. Most cases occur in patients with risk factors for fracture and concomitant hypovitaminosis D. References: Chary-Valckenaere I, Blum A, Péré P, GRAUBUENDEN B, Pourel J, Gaucher A. Insufficiency fractures of the ilium. Rev. Rhum. (Engl. Ed) 1997; 64 (10): 542-8. Disclosure of Interest: None Declared